2023
DOI: 10.1002/ctm2.1198
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5‐mediated m6A demethylation of TIRAP mRNA promotes radiation‐induced liver fibrosis and decreases radiosensitivity of hepatocellular carcinoma

Abstract: Background Radiation‐induced hepatic stellate cell (HSC) activation promotes radiation‐induced liver fibrosis (RILF), a complication for hepatocellular carcinoma (HCC) radiotherapy. The demethylase alpha‐ketoglutarate‐dependent dioxygenase alkB homolog 5 (ALKBH5) decreases N6‐methyladenylate methylation (m 6 A) modification of RNA, while its role in regulating RILF pathogenesis and HCC radiosensitivity remains unknown. Methods Methylated RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Therefore, IOX1 upregulated T reg recruitment and inhibited inflammatory cells via increasing CCl28 expression, which alleviated Ischemia–reperfusion injury-stimulated renal fibrosis mouse model 177 . It is noteworthy that radiation-induced ALKBH5 could inhibit toll-interleukin 1 receptor domain containing adaptor protein (TIRAP) m 6 A methylation and thus activate NF- κ B–Smad2 pathway to activate HSCs 178 . It may attract interest whether ALKBH5 inhibitors could disturb TIRAP–NF- κ B–Smad2 pathway to suppress HSC activation and liver fibrosis for further studies.…”
Section: Promising Therapeutic Directions and Challenges Aheadmentioning
confidence: 99%
“…Therefore, IOX1 upregulated T reg recruitment and inhibited inflammatory cells via increasing CCl28 expression, which alleviated Ischemia–reperfusion injury-stimulated renal fibrosis mouse model 177 . It is noteworthy that radiation-induced ALKBH5 could inhibit toll-interleukin 1 receptor domain containing adaptor protein (TIRAP) m 6 A methylation and thus activate NF- κ B–Smad2 pathway to activate HSCs 178 . It may attract interest whether ALKBH5 inhibitors could disturb TIRAP–NF- κ B–Smad2 pathway to suppress HSC activation and liver fibrosis for further studies.…”
Section: Promising Therapeutic Directions and Challenges Aheadmentioning
confidence: 99%
“…By modulating the expression of cancer-related genes, RNA methylation drives the regulation of a wide range of processes in HCC progression, such as cell proliferation, invasion, resistance to therapy, tumor growth, and metastasis. Several studies have explored the interaction between RNA methylation and HCC progression and confirmed the great potential of targeted RNA methylation in vitro and in animal models (Table 2 ) [ 71 , 73 , 79 , 80 ]. Thus, a thorough understanding of molecular pathology of RNA methylation in HCC is essential for the improvement of treatment landscape and clinical outcomes in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ALKBH5 directly downregulates LINC02551, which slows down the growth and metastasis of HCC cells by weakening the stability of DEAD box protein 24 (DDX24) [ 72 ]. During radiation therapy for HCC, radiation-induced hepatic stellate cells upregulate ALKBH5 to mediate the methylation modification of tollinterleukin 1 receptor domain containing adaptor protein (TIRAP), resulting in reduced apoptosis and radiosensitivity of HCC cells [ 71 ]. In HCC HepG2 and Hep3B cells, circGPR137B has been identified as a sponge for miR-4739 and FTO as a direct target of miR-4739, forming a positive feedback loop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between TME and cancer cells can enhance the malignant properties of tumors, including proliferation, metastasis, and therapy resistance ( Hosaka et al, 2020 ; Tian et al, 2021 ). In addition, TME can also lead to abnormal angiogenesis and promote immunosuppression ( Chen et al, 2023 ). Therefore, further study of TME of HCC may be helpful for the development of therapeutic methods for HCC.…”
mentioning
confidence: 99%